Criterion A of the AMPD in HiTOP - Widiger, Thomas A.; Bach, Bo; Chmielewski, Michael; Clark, Lee Anna; DeYoung, Colin; Hopwood, Christopher J.; Kotov, Roman; Krueger, Robert F.; Miller, Joshua D.; Morey, Leslie C.; Mullins-Sweatt, Stephanie N.; Patrick, Christopher J.; et al. (Journal of personality assessment, 2019)
The categorical model of personality disorder classification in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (5th ed. [DSM-5]; American Psychiatric Association, 2013 ) is highly and fundamentally problematic. Proposed for DSM-5 and provided within Section III (for Emerging Measures and Models) was the Alternative Model of Personality Disorder (AMPD) classification, consisting of Criterion A (self-interpersonal deficits) and Criterion B (maladaptive personality traits). A proposed alternative to the DSM-5 more generally is an empirically based dimensional organization of psychopathology identified as the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al., 2017 ). HiTOP currently includes, at the highest level, a general factor of psychopathology. Further down are the five domains of detachment, antagonistic externalizing, disinhibited externalizing, thought disorder, and internalizing (along with a provisional sixth somatoform dimension) that align with Criterion B. The purpose of this article is to discuss the potential inclusion and placement of the self-interpersonal deficits of the DSM-5 Section III Criterion A within HiTOP.